A reading in the book (Al-Madinah Al-Munawwarah: Its Urban Development and Architectural Heritage) by Dr. Salih Lamei Mustafa | قراءة في كتاب (المدينة المنورة تطورها العمراني وتراثها المعماري) للدكتور صالح لمعي مصطفى - Al-Madinah Al-Munawwarah Research and Studies Center | مركز بحوث ودراسات المدينة المنورة (Al-Madinah Al-Munawwarah Research and Studies Center | مركز بحوث ودراسات المدينة المنورة, 2023)
Research topic: pp. 175-186 | موضع البحث: ص 175 - 186